From Tsushima to Berlin and the Kurile Islands. Russian and Soviet Naval Power, 1905 - 1945 - Muraviev, Alexey (Taylor & Francis, 2025)
This handbook brings together historical and contemporary essays about Soviet and Russian military studies, to offer a comprehensive volume on the topic.